2013
DOI: 10.1371/journal.pone.0077578
|View full text |Cite
|
Sign up to set email alerts
|

In-Vivo Efficacy of Compliant 3D Nano-Composite in Critical-Size Bone Defect Repair: a Six Month Preclinical Study in Rabbit

Abstract: Bone defects above critical size do not heal completely by itself and thus represent major clinical challenge to reconstructive surgery. Numerous bone substitutes have already been used to promote bone regeneration, however their use, particularly for critical-sized bone defects along with their long term in vivo safety and efficacy remains a concern. The present study was designed to obtain a complete healing of critical-size defect made in the proximal tibia of New Zealand White rabbit, using nano-hydroxyapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…This flaw phenomenon is frequently appearing in polymer-based scaffold and coated framework, as developed in this study. Many studies have reported the enhancement of mechanical characteristics of scaffolds by integration of inorganic biological substances (44)(45)(46). Gelatin, dextrin and dextran are known natural polymers that form a fragile hydrogel like scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…This flaw phenomenon is frequently appearing in polymer-based scaffold and coated framework, as developed in this study. Many studies have reported the enhancement of mechanical characteristics of scaffolds by integration of inorganic biological substances (44)(45)(46). Gelatin, dextrin and dextran are known natural polymers that form a fragile hydrogel like scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…Microarchitectural parameters including, bone volume fraction (BV/TV), trabecular thickness (Tb.Th), trabecular separation (Tb.Sp), trabecular number (Tb.N) and structure model index (SMI) were quantified as described before [33,34] Loading of MSC with 3D Scaffold at Fractured Site To study the therapeutic effect of cont MSC and Ovx MSC in equal number with 3D scaffold at fractured site in female rats was evaluated. A 3-D nano-hydroxyapatite/gelatin/ carboxymethyl chitin (n-HA/gel/CMC) scaffold constructs were prepared by solvent casting method combined with glutaraldehyde vapour crosslinking and freeze drying method as described before [35,36]. The scaffolds were removed from the sterile patches and wetted with blood that oozed out from the incision during surgery.…”
Section: Micro-computed Tomography (μCt)mentioning
confidence: 99%
“…CMC is a polysaccharide based hydrogel that when incorporated with hydroxyapatite in a CMC-based hydrogel provides excellent tissue engineering function [14]. In 2013, Sagar et al developed a nanohydroxyapatite/gelatin and chemically carboxymethylated chitin scaffold that enhanced osteoblastic activity and mineralization [15]. However, cellulose-based hydrogels lack good mechanical proprieties for clinical use [14].…”
Section: Introductionmentioning
confidence: 99%